2009
DOI: 10.1111/j.1365-3164.2009.00799.x
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary cutaneous mucinosis in shar pei dogs is associated with increased hyaluronan synthase‐2 mRNA transcription by cultured dermal fibroblasts

Abstract: Shar pei dogs are known for the distinctive feature of thick, wrinkled skin as a consequence of high dermal mucin content. Excessive dermal deposition of mucinous substance leading to severe skin folding, and/or to the more severe vesicular form characterized by dermal vesicles or bullae, is highly prevalent in this breed and is known as idiopathic mucinosis. Hyaluronic acid (HA) is the main component that accumulates in the dermis, and high levels of HA have also been detected in the serum of shar pei dogs. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 19 publications
1
32
0
6
Order By: Relevance
“…HAS2 is integral for making hyaluronan, a major component of skin (Laurent & Fraser 1992). Interestingly, previous work suggested that Shar-Pei dogs have an excess of hyaluronan in their skin (Zanna et al 2009) and that excess hyaluronan is associated with abnormal skin phenotypes in both dogs and man (Ramsden et al 2000). In the Shar-Pei, the excess hyaluronan linked to skin wrinkling may occur by cis -acting misregulation of HAS or its negative regulator, HAS2 antisense RNA1, in a manner that is dose dependent in terms of copy number (Olsson et al 2011).…”
Section: Genetics Of Canine Diseases Inform Human Conditionsmentioning
confidence: 99%
“…HAS2 is integral for making hyaluronan, a major component of skin (Laurent & Fraser 1992). Interestingly, previous work suggested that Shar-Pei dogs have an excess of hyaluronan in their skin (Zanna et al 2009) and that excess hyaluronan is associated with abnormal skin phenotypes in both dogs and man (Ramsden et al 2000). In the Shar-Pei, the excess hyaluronan linked to skin wrinkling may occur by cis -acting misregulation of HAS or its negative regulator, HAS2 antisense RNA1, in a manner that is dose dependent in terms of copy number (Olsson et al 2011).…”
Section: Genetics Of Canine Diseases Inform Human Conditionsmentioning
confidence: 99%
“…Regarding the other outlier SNPs identified in their study, one of the highest F ST values was only found in the Shar-Pei breed, which is characterized by its distinctive skin-folding phenotype. The region where the high F ST signal was found contains several genes, including HAS2, the expression of which had previously been associated with skin wrinkling in this breed [23]. A recently discovered duplication upstream of this gene appears to be responsible for the wrinkling phenotype [24].…”
Section: Selective Forcesmentioning
confidence: 99%
“…The distribution of genotypes actually confirmed the high incidence of SPAID in meatmouth Shar-Pei types but also detected SPAID-affected bonemouth types. In addition, HAS2 mRNA was further shown to be highly expressed in cells of severely folded skin and skin vesicles derived from vesicular hyaluronosis due to an accumulation of hyaluronic acid [33, 34]. Our pathohistologic examinations showed that both SPAID-affected and SPAID-unaffected dogs harboured signs of cutaneous mucinosis as a result of hyaluronic acid accumulation.…”
Section: Discussionmentioning
confidence: 92%